垂直式业务场景中业务资源确定方法、装置及存储介质 (2024)
本申请实施例公开了垂直式业务场景中业务资源确定方法、装置及存储介质。上述方法包括确定业务关联主体和业务关联账户；确定垂直式业务场景对应的业务资源配置策略，上述业务资源配置策略包括预计支出资源的计算方法和资源配置风险的计算方法；以上述业务关联主体和上述业务关联账户为参考数据，基于上述预计支出资源的计算方法确定目标预计支出资源；以上述业务关联账户为参考数据，基于上述资源配置风险的计算方法确定目标资源配置风险参数；根据上述目标预计支出资源和上述目标资源配置风险参数，确定上述垂直式业务场景中的业务资源。本申请实施例可以自动确定业务资源，从而提升业务资源确定效率和客观程度。 The embodiment of the invention discloses a service resource determination method and device in a vertical service scene and a storage medium. The method comprises the following steps: determining a service association subject and a service association account; determining a service resource allocation strategy corresponding to the vertical service scene, wherein the service resource allocation strategy comprises a calculation method of predicted expenditure resources and a calculation method of resource allocation risks; determining a target predicted expenditure resource based on the calculation method of the predicted expenditure resource by taking the service association subject and the service association account as referen